Emergency physicians’ and nurses’ perception on the adequacy of emergency calls for nursing home residents: a non-interventional prospective study - Lemoyne, Sabine; Van Bastelaere, Joanne; Nackaerts, Sofie; Verdonck, Philip; Monsieurs, Koenraad; Schnaubelt, Sebastian (Frontiers in Medicine, 2024)
Introduction A considerable percentage of daily emergency calls are for nursing home residents. With the ageing of the overall European population, an increase in emergency calls and interventions in nursing homes (NH) is to be expected. A proportion of these interventions and hospital transfers may be preventable and could be considered as inappropriate by prehospital emergency medical personnel. The study aimed to understand Belgian emergency physicians’ and emergency nurses’ perspectives on emergency calls and interventions in NHs and investigate factors contributing to their perception of inappropriateness. Methods An exploratory non-interventional prospective study was conducted in Belgium among emergency physicians and emergency nurses, currently working in prehospital emergency medicine. Electronic questionnaires were sent out in September, October and November 2023. Descriptive statistics were used to analyze the overall results, as well as to compare the answers between emergency physicians and emergency nurses about certain topics. Results A total of 114 emergency physicians and 78 nurses responded to the survey. The mean age was 38 years with a mean working experience of 10 years in prehospital healthcare. Nursing home staff were perceived as understaffed and lacking in competence, with an impact on patient care especially during nights and weekends. General practitioners were perceived as insufficiently involved in the patient’s care, as well as often unavailable in times of need, leading to activation of Emergency Medical Services (EMS) and transfers of nursing home residents to the Emergency Department (ED). Advance directives were almost never available at EMS interventions and transfers were often not in accordance with the patient’s wishes. Palliative care and pain treatment were perceived as insufficient. Emergency physicians and nurses felt mostly disappointed and frustrated. Additionally, differences in perception were noted between emergency physicians and nurses regarding certain topics. Emergency nurses were more convinced that the nursing home physician should be available 24/7 and that transfers could be avoided if nursing home staff had more authority regarding medical interventions. Emergency nurses were also more under the impression that pain management was inadequate, and emergency physicians were more afraid of the medical implications of doing too little during interventions than emergency nurses. Suggestions to reduce the number of EMS interventions were more general practitioner involvement (82%), better nursing home staff education/competences (77%), more nursing home staff (67%), mobile palliative care support teams (65%) and mobile geriatric nursing intervention teams (52%). Discussion and conclusion EMS interventions in nursing homes were almost never seen as necessary or indicated by emergency physicians and nurses, with the appropriate EMS level almost never being activated. The following key issues were found: shortages in numbers and competence of nursing home staff, insufficient primary care due to the unavailability of the general practitioner as well as a lack of involvement in patient care, and an absence of readily available advance directives. General practitioners should be more involved in the decision to call the Emergency Medical Services (EMS) and to transfer nursing home residents to the Emergency Department. Healthcare workers should strive for vigilance regarding the patients’ wishes. The emotional burden of deciding on an avoidable hospital admission of nursing home residents, perhaps out of fear for medico-legal consequences if doing too little, leaves the emergency physicians and nurses frustrated and disappointed. Improvements in nursing home staffing, more acute and chronic general practitioner consultations, and mobile geriatric and palliative care support teams are potential solutions. Further research should focus on the structural improvement of the above-mentioned shortcomings.